2017
DOI: 10.24326/asphc.2017.5.11
|View full text |Cite
|
Sign up to set email alerts
|

SCREENING OF THREE SAFFLOWER (Carthamus tinctorius L.) CULTIVARS UNDER BORON STRESS

Abstract: Excess of boron in soil and irrigation water is a serious constrain to crop production in many areas of the World as well as in Turkey. A pot experiment was carried out with to screen safflower cultivars in order to investigate the effects of boron toxicity stress on early growth and ions composition. Three safflower cultivars (Carthamus tinctorius cv. Balci, Yenice, Remzi Bey) were grown in pots containing alkaline and potassium rich soil, additionally supplemented with 0, 4, 8, 16, 32, 64 and 128 mg kg -1 bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Day and coauthors carried out a study on the effects of boron toxicity with the Remzibey, Yenice, and Balcı cultivars [65]. They found that the Balcı cultivar has the potential to be used for the phytoremediation of B toxic soils (including alkaline soils and those with high available K levels).…”
Section: Discussionmentioning
confidence: 99%
“…Day and coauthors carried out a study on the effects of boron toxicity with the Remzibey, Yenice, and Balcı cultivars [65]. They found that the Balcı cultivar has the potential to be used for the phytoremediation of B toxic soils (including alkaline soils and those with high available K levels).…”
Section: Discussionmentioning
confidence: 99%
“…With sulphur doses, K content was recorded between 0.56-0.60%. Potassium regulates the osmotic pressure of the plant and it has an important role in starch synthesis In similar studies related to the subject; Day et al (2017) determined that the K content was obtained between 45.4-72.1 g/kg from the Remzibey cultivar, while K content was obtained between 52.6-69.2 g/kg from the Yenice cultivar. In related to sulphur applications, Yılmaz (2017) determined that the highest K content was obtained as 4.67 % from 20 kg S ha -1 .…”
Section: Resultsmentioning
confidence: 98%
“…al., 2011). Day et al (2017) recorded that Ca content was determined between 7.7-11.0 g/kg from the Remzibey cultivar, while Ca content was obtained between 8.7-12.2 g/kg from the Yenice cultivar. In addition, it was recorded that obtained from control (0 kg S ha -1 ) applications as 1.22 % highest Ca content of canola plant, in a study carried out by Yılmaz (2007).…”
Section: Resultsmentioning
confidence: 99%
“…Sunflower is among the commonly cultivated oilseed crops in Türkiye [6,7] with a place among the alternative crops like safflower and others whose cultivation is increasing due to changing irrigation regimes, plant diseases, pests, salinity and boron toxicity problems. Safflower has deep root growth which enables the use of deep soil water; especially in areas suffering from salinity and it can also take part in crop rotation and phytoremediation to reduce salinity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%